# What is the equation of the line normal to # f(x)=-sqrt((x+1)(x+3)# at #x=0#?

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the line normal to f(x) = -sqrt((x+1)(x+3)) at x=0 is y = -1.

By signing up, you agree to our Terms of Service and Privacy Policy

- What is the equation of the normal line of #f(x)=x^2-x+1/x# at #x = 2#?
- How do you find the average rate of change of #y=-1/(x+2)# over [-1,-1/2]?
- How do you use the limit definition to find the slope of the tangent line to the graph # f(x) = x^2#?
- How do you find f'(x) using the definition of a derivative for #f(x)=cos x#?
- What is the slope of #f(x)=-X/e^(x-x^3) # at #x=-1#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7